Importancia del código de convivencia en el cumplimiento de los estándares de calidad de desempeño directivo de la escuela de educación básica Canadá del cantón Latacunga en el periodo lectivo 2013-2014 - Shigui Quishpe, María Lidia (2015)
The following research, previous to get the Sciences Education science degree has as objective to give and learn the code importance about standards coexistence like an fulfillment from directors performance quality at “Canadá” Basic Education Schools in the Latacunga canton during 2013 - 2014. So aware, practicing values is very important about ethical and moral values in the education job for that reason is a goal to get an improvement with the application of regulatory processes Matrix for the application of coexistence code in the fulfillment from the of quality standards in the education community for the different levels and modalities; which should be made, applied, evaluated and enhanced in form to keep going. The coexistence code has as purpose in their application the strengthening and integral developing of the community actors, at the exercise of their rights duties for harmonically coexist with education quality.